2022
DOI: 10.1101/2022.10.10.22280894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the distribution of zero-dose children to assess the performance of vaccine delivery strategies and their relationships with measles incidence in Nigeria

Abstract: Geographically precise identification and targeting of populations at risk of vaccine-preventable diseases has gained renewed attention within the global health community over the last few years. District level estimates of vaccination coverage and corresponding zero-dose prevalence constitute a potentially useful evidence base to evaluate the performance of vaccination strategies. These estimates are also valuable for identifying missed communities, hence enabling targeted interventions and better resource al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In a tertiary hospital setting in Pakistan, Rahman et al reported that the MCV1 and MCV2 vaccination rate was the single most affected antigen within the EPI schedule, with lowest recovery when comparing percentage change for COVID-19 interruption and early recovery with pre-COVID baseline vaccination rates (EPI vaccines −36.2% to −11.7%; MCV1 -40.9% to −17.8%; MCV2 -48.6% to −20.7%) [ 48 ]. Utazi et al [ 57 ] hypothesised that MCV1 and MCV2 showed a disproportionate reduction over other EPI vaccine antigens because they are administered later in life, as opposed to those given at birth (potentially with a healthcare provider present) or in the first few months of life. Contrarily, studies in Pakistan, Ghana and Sierra Leone identified a greater reduction in doses given at the start of the childhood schedule and attributed this as due to a reduction in births in hospitals [ 26 , 43 , 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a tertiary hospital setting in Pakistan, Rahman et al reported that the MCV1 and MCV2 vaccination rate was the single most affected antigen within the EPI schedule, with lowest recovery when comparing percentage change for COVID-19 interruption and early recovery with pre-COVID baseline vaccination rates (EPI vaccines −36.2% to −11.7%; MCV1 -40.9% to −17.8%; MCV2 -48.6% to −20.7%) [ 48 ]. Utazi et al [ 57 ] hypothesised that MCV1 and MCV2 showed a disproportionate reduction over other EPI vaccine antigens because they are administered later in life, as opposed to those given at birth (potentially with a healthcare provider present) or in the first few months of life. Contrarily, studies in Pakistan, Ghana and Sierra Leone identified a greater reduction in doses given at the start of the childhood schedule and attributed this as due to a reduction in births in hospitals [ 26 , 43 , 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety surrounding vaccination has also increased in response to misleading information spread on social media [ 70 ]. Increasing vaccine hesitancy was cited as a specific challenge for vaccination campaigns in multiple included studies [ 10 , 43 , 44 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations